A Double-Edged Sword: How Oncogenes and Tumor Suppressor Genes Can Contribute to Chromosomal Instability - Orr, Bernardo; Compton, Duane A. (Frontiers in Oncology, 2013)
Most solid tumors are characterized by abnormal chromosome numbers (aneuploidy) and karyotypic profiling has shown that the majority of these tumors are heterogeneous and chromosomally unstable. Chromosomal instability (CIN) is defined as persistent mis-segregation of whole chromosomes and is caused by defects during mitosis. Large-scale genome sequencing has failed to reveal frequent mutations of genes encoding proteins involved in mitosis. On the contrary, sequencing has revealed that most mutated genes in cancer fall into a limited number of core oncogenic signaling pathways that regulate the cell cycle, cell growth and apoptosis. This led to the notion that the induction of oncogenic signaling is a separate event from the loss of mitotic fidelity, but a growing body of evidence suggests that oncogenic signaling can deregulate cell cycle progression, growth and differentiation as well as cause CIN. These new results indicate that the induction of CIN can no longer be considered separately from the cancer-associated driver mutations. Here we review the primary causes of CIN in mitosis and discuss how the oncogenic activation of key signal transduction pathways contributes to the induction of CIN.